Advanced progress in the genetic modification of the oncolytic HSV-1 virus - Zhou, Mi; Shen, Zhenyu (Frontiers in Oncology, 2025)
The use of replication-competent viruses for selective tumor oncolysis while sparing normal cells marks a significant advancement in cancer treatment. HSV-1 presents several advantages that position it as a leading candidate for oncolytic virotherapies. Its large genome can accommodate insertions over 30 kb or deletions of multiple virulence genes without compromising lytic replication in tumor cells. Additionally, anti-herpes drugs can inhibit its replication during accidental infections. Importantly, HSV-1 does not integrate into the host genome and cause mutations. The HSV-1 genome can be modified through genetic engineering in two main ways: first, by reducing infectivity and toxicity to normal cells via limited replication and assembly, altered protein-virus receptor binding, and minimized immune evasion; second, by enhancing anticancer activity through disruption of tumor cell metabolism, induction of autophagy, improved immune recognition, and modification of the tumor microenvironment. In this mini-review, we systematically examine genetic modification strategies for oncolytic HSV-1 while highlighting advancements from these modifications. Certain genetic alterations have shown efficacy in improving clinical outcomes for HSV-1-based therapies. These modifications include silencing specific genes and inserting exogenous genes into the HSV-1 genome. The insertion of exogenous genes has increasingly been used to develop new oncolytic HSV-1 variants. Finally, we discuss limitations associated with oncolytic virotherapy at the conclusion of this review. As more clinical trials explore newly engineered therapies, they are likely to yield breakthroughs and promote broader adoption for cancer treatment.